Complex Effects of the ZSCAN21 Transcription Factor on Transcriptional Regulation of α-Synuclein in Primary Neuronal Cultures and in Vivo - Dermentzaki, Georgia (J Biol Chem, 2016)
α-Synuclein, a presynaptic neuronal protein encoded by the SNCA gene, is strongly implicated in Parkinson disease (PD). PD pathogenesis is linked to increased SNCA levels; however, the transcriptional elements that control SNCA expression are still elusive. Previous experiments in PC12 cells demonstrated that the transcription factor zinc finger and SCAN domain containing 21 (ZSCAN21) plays an important regulatory role in SNCA transcription. Currently, we characterized the role of ZSCAN21 in SNCA transcription in primary neuronal cultures and in vivo. We found that ZSCAN21 is developmentally expressed in neurons in different rat brain regions. We confirmed its binding in the intron 1 region of SNCA in rat cortical cultures. Lentivirus-mediated silencing of ZSCAN21 increased significantly SNCA promoter activity, mRNA, and protein levels in such cultures. In contrast, ZSCAN21 silencing reduced SNCA in neurosphere cultures. Interestingly, ZSCAN21 overexpression in cortical neurons led to robust mRNA but negligible protein expression, suggesting that ZSCAN21 protein levels are tightly regulated post-transcriptionally and/or post-translationally in primary neurons. Efficient adeno-associated virus-mediated knockdown of ZSCAN21 in the postnatal and adult hippocampus, an area linked with non-motor PD symptoms, revealed no significant alterations in SNCA levels. Overall, our study demonstrates that ZSCAN21 is involved in the transcriptional regulation of SNCA in primary neuronal cultures, but the direction of the effect is variable, likely depending on neuronal maturation. However, the unaltered SNCA levels observed following ZSCAN21 down-regulation in the rat brain, possibly due to compensatory mechanisms, imply that ZSCAN21 is not a master regulator of SNCA in vivo.